2018
DOI: 10.1186/s12885-018-4659-0
|View full text |Cite
|
Sign up to set email alerts
|

Levels and prognostic impact of circulating markers of inflammation, endothelial activation and extracellular matrix remodelling in patients with lung cancer and chronic obstructive pulmonary disease

Abstract: BackgroundThe development of both chronic obstructive pulmonary disease (COPD) and lung cancer (LC) is influenced by smoking related chronic pulmonary inflammation caused by an excessive innate immune response to smoke exposure. In addition, the smoking induced formation of covalent bonds between the carcinogens and DNA and the accumulation of permanent somatic mutations in critical genes are important in the carcinogenic processes, and can also induce inflammatory responses.How chronic inflammation is mirrore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 22 publications
1
23
0
Order By: Relevance
“…What is more, previous studies have demonstrated the role of CD147 in regulating inflammatory responses in a variety of diseases, including lung inflammation [1820]. Berg et al found that serum levels of CD147 were high in COPD patients [21]. Since MMP9 and p38 MAPK are indispensable signaling molecules in the regulation of MUC5AC secretion, we hypothesize that CD147 may take part in MUC5AC production in COPD through these signaling molecules.…”
Section: Introductionmentioning
confidence: 68%
“…What is more, previous studies have demonstrated the role of CD147 in regulating inflammatory responses in a variety of diseases, including lung inflammation [1820]. Berg et al found that serum levels of CD147 were high in COPD patients [21]. Since MMP9 and p38 MAPK are indispensable signaling molecules in the regulation of MUC5AC secretion, we hypothesize that CD147 may take part in MUC5AC production in COPD through these signaling molecules.…”
Section: Introductionmentioning
confidence: 68%
“…In contrast, a higher level of sTNFR1 is associated with better survival in lung cancer patients with and without chronic obstructive pulmonary disease. [51] In addition to its role in cancer, sTNFR1 is strongly associated with other diseases, such as cardiovascular mortality [52] and nonrelapse mortality after hematopoietic cell transplantation. [53] EVs are regarded as a molecular signature of the parental cells and provide insight about the origin and functions of the parental cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ROC analysis indicated that PTX3 could discriminate between cancer patients and heavy smokers at high risk for lung cancer (127). Similarly, high PTX3 levels were correlated with worse progression-free survival in patients with lung cancer and chronic obstructive pulmonary disease (132), and with overall survival and disease-free survival in small-cell lung carcinoma (SCLC) (133). A recent study on 1358 individuals at high risk for lung cancer demonstrated that PTX3 levels were not predictive of pathology occurrence (128).…”
Section: Ptx3 As Marker Of Cancer Progressionmentioning
confidence: 99%